Blood-Based Protein Changes in Childhood Are Associated With Increased Risk for Later Psychotic Disorder: Evidence From a Nested Case–Control Study of the ALSPAC Longitudinal Birth Cohort. (27th July 2017) - English, Jane A; Lopez, Lorna M; O'Gorman, Aoife; Föcking, Melanie; Hryniewiecka, Magdalena; Scaife, Caitriona; Sabherwal, Sophie; Wynne, Kieran; Dicker, Patrick; Rutten, Bart P F; Lewis, Glynn; Zammit, Stanley; et al.
Abstract: The identification of early biological changes associated with the psychotic disorder (PD) is important as it may provide clues to the underlying pathophysiological mechanisms. We undertook the first proteomic profiling of blood plasma samples of children who later develop a PD. Participants were recruited from the UK Avon Longitudinal Study of Parents and Children (ALSPAC) cohort who also participated in psychiatric assessment interviews at age 18. Protein expression levels at age 11 were compared between individuals who developed PD at age 18 ( n = 37) with population-based age-matched controls ( n = 38). Sixty out of 181 plasma proteins profiled were found to be differentially expressed ( P < .05) in children with an outcome of the PD. Thirty-four of these proteins were found to be differentially expressed following correction for multiple comparisons. Pathway analysis implicated the complement and coagulation cascade. A second, targeted proteomic approach was used to verify these findings in age 11 plasma from subjects who reported psychotic experiences at age 18 ( n = 40) in comparison to age-matched controls ( n = 66). Our findings indicate that the complement and coagulation system is dysregulated in the blood during childhood before the development of the PD.